Pengaruh Insentif dan Motivasi Terhadap Komitmen Kinerja Guru dari Pengelolaan Dana BOS pada SMP YPK Syaloom Kota Sorong - Herningsih, Herningsih; Priyanti, Rini Yayuk; F. Wanggai, Azarya M. (Journal of Comprehensive Science, 2025)
This study aims to analyze the influence of incentives and motivation on teachers' commitment and performance in the management of School Operational Assistance (BOS) funds at YPK Syaloom Junior High School, Sorong City. The research employed a quantitative method with a survey approach. Data were collected through questionnaires distributed to teachers and analyzed using multiple linear regression analysis techniques. The findings reveal that incentives and motivation have a positive and significant impact on teachers' commitment and performance. Regular and workload-appropriate incentives were proven to enhance teachers' dedication in carrying out their duties. Additionally, both internal and external motivation played a crucial role in boosting teachers' work enthusiasm. High teacher commitment was also found to mediate and strengthen the relationship between incentives, motivation, and teacher performance. This study underscores the importance of effective and transparent BOS fund management to improve teachers' welfare through adequate incentives and efforts to enhance work motivation. Consequently, schools can create a conducive work environment that promotes the improvement of educational quality.